Natal Fruit Fly, Natal Fly, Ceratitis rosa Karsch (Insecta: Diptera: Tephritidae) - Howard V. Weems; Thomas R. Fasulo (EDIS)
The Natal fruit fly is a pest of orchard fruits throughout much of KwaZulu Natal Province, Republic of South Africa, and is considered to be the most common fruit fly of economic importance in Zimbabwe. 50 to 100 percent of plums were reportedly infested in a South African locality one year despite the application of control measures. Although it never has been captured as an escapee in the United States, it continues to constitute a potential threat to Florida agriculture. If it were accidentally introduced into Florida and allowed to gain a foothold, the Natal fruit fly could prove to be fully as serious a menace as the Mediterranean fruit fly. This revised 3-page fact sheet was written by H. V. Weems, Jr. and T. R. Fasulo, and published by the UF Department of Entomology and Nematology, March 2012.